174 Cardiac magnetic resonance imaging in patients with chest pain, troponin increase and unobstructed coronary arteries; a study of real-world adherence to guidelines from a large UK district general hospital during the COVID-19 pandemic. (4th June 2021) - Olubodun, Oluwaseun; Azeez, Shereen; Dhera, Karishma; Shearman, Harriet; Elkington, Andrew; Bull, Sacha
Abstract : Background: The 2020 ESC Taskforce guidelines made a level I recommendation for the use of cardiac magnetic resonance (CMR) in patients with suspected myocardial infarction with non-obstructive coronary arteries (MINOCA). CMR is a powerful diagnostic tool that can discriminate between myocardial infarction, Takostubo and myocarditis; myocardial oedema is best seen when a cardiac MR scan is carried out within 14 days of the initial Troponin positive event and normally subsides after 6 weeks. Access to CMR during the COVID pandemic year was restricted at the height of the pandemic. Purpose: The purpose of this study was three fold. 1. To examine what proportion of patients with a rise and fall in Troponin and unobstructed coronary arteries were offered a CMR scan in our hospital during the year of 2020. 2. To examine the waiting times for a CMR scan during this year 3. To establish in what proportion of patients the CMR scan changed the diagnosis and management of the patients. Methods: This is a retrospective cohort study of all patients that presented to the Royal Berkshire Hospital with chest pain, a troponin rise and unobstructed coronaries on invasive angiogram between January and December of 2020. We collected data on demographics, the degree of troponin rise, echocardiography results, the discharge diagnosis and details of CMR findings (if performed). For quantitative data analysis, the number of days between presentation and CMR imaging was collated, as was the incidence of change of diagnosis and or management. Results: Complete data was available for 104 patients who presented to the Royal Berkshire Hospital with chest pain between 6th January and 21st December 2020. All underwent coronary angiography. Of the patients included, 55.8% (58) were men and 44.2% (46) were women - all between 29 and 89 years of age. 61% of these patients had an ECHO as an inpatient, whilst a further 26% had a Vscan performed. Overall 87% of these patients had a Vscan or ECHO. Of the patients meeting the criteria, 31% of them received an inpatient (16%) or urgent outpatient (84%) CMR, with the average time between presentation and image being 47.3 days. Finally, 59% of diagnosis made on discharge were altered by findings on CMR, with 47% of management plans changed as a result of findings. Final diagnoses, following CMR, can be seen in figure 1 . Subgroup analyses were performed on those that displayed initial raised troponins that remained static during admission, and those that received discharge diagnoses of Takotsubo or myocarditis/ pericarditis/ myopericarditis. Conclusions: During 2020, the majority of patients (70%) with Troponin rise and unobstructed coronary arteries did not undergo CMR scanning in our hospital. Of the patients offered a CMR scan during the year of 2020, the scan changed the diagnosis in the majority of patients (59% ) but the wait for CMR was considerable (average of 47.3 days). This study suggests that in 2020, in our hospital the majority of patients may have ended up with suboptimal treatment following an admission with chest pain, troponin rise and unobstructed coronary arteries due to reduced access to CMR. This may be, in part, down to the impact of COVID on access to CMRs during the height of the pandemic. Conflict of Interest: Nil